Study of effectiveness of combined test Pap smear, visual inspection with acetic acid and Lugols iodine for mass screening of premalignant and malignant lesions of cervix - V. S., Nivedhitha; R., Sankareswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cancer cervix is the leading cause of morbidity and mortality in developing nations. This study aims to evaluate the usefulness of visual inspection with acetic acid (VIA) and Lugols iodine (VILI) as adjunct to improve the sensitivity of cervical cytology with Pap smear and to enhance the test performance. Methods: Study was conducted in Gynaec OPD clinic in SVMCH & RC, Ariyur, Pondicherry during the period of January 2015 to June 2015. 350 patients enrolled in the study, 10 patients (2.8%) had positive Pap smear, 96 patients (27.4%) had inflammatory smears and 244 (69.7%) had normal smear. VIA was positive in 29 patients (8.2%). VILI was positive in 50 patients (14.2%). Results: Sensitivity of Pap smear = 40% (CI 19.82-64.25%), sensitivity of VIA=40% (CI 19.82-64.25%), sensitivity of VILI = 86.66% (CI 62.12-92.26%), sensitivity of VIA+VILI tests = 86.66% (CI 62.12-96.26), sensitivity of combination tests (Pap + VIA + VILI) = 100% (CI 79.60-100.00). As shown by our study, VILI picked up the maximum premalignant lesions confirmed by cervical biopsy (15 premalignant lesions on cervical biopsy, and VILI is positive in 13 cases) and 6 were picked up by VIA, whereas Pap was positive in 6 patients. Conclusions: This study concludes that the effectiveness of cervical cancer screening can be improved by a combination test of Pap, VILI and VIA, even in tertiary centers in India.